Development and Validation of Precipitation Enhanced Densities for the Empirical Canadian High Arctic Ionospheric Model. Issue 10 (5th October 2021) - Watson, C.; Themens, D. R.; Jayachandran, P. T.
Abstract: The Empirical Canadian High Artic Ionospheric Model (E‐CHAIM) provides the four‐dimensional ionosphere electron density at northern high latitudes (>50° geomagnetic latitude). Despite its emergence as the most reliable model for high‐latitude ionosphere density, there remain significant deficiencies in E‐CHAIM's representation of the lower ionosphere (below ∼200 km) due to a sparsity of reliable measurements at these altitudes, particularly during energetic particle precipitation events. To address this deficiency, we have developed a precipitation component for E‐CHAIM to be driven by satellite‐based far‐ultraviolet (FUV) imager data. Satellite observations of FUV emissions may be used to infer the characteristics of energetic particle precipitation and subsequently calculate the precipitation‐enhanced ionization rates and ionosphere densities. In order to demonstrate the improvement of E‐CHAIM's ionosphere density representation with the addition of a precipitation component, this paper presents comparisons of E‐CHAIM precipitation‐enhanced densities with ionosphere density measurements of three auroral region incoherent scatter radars (ISRs) and one polar cap ISR. Calculations for 29, 038 satellite imager and ISR conjunctions during the years 2005–2019 revealed that the root‐mean‐square difference between E‐CHAIM and ISR measurements decreased by up to 2.9 × 10 10  ele/m 3 (altitude dependent) after inclusion of the precipitation component at auroral sites, and by 2.6 × 10 9  ele/m 3 in the polar cap. Improvements were most substantial in the winter season and during active auroral conditions. The sensitivity of precipitation‐enhanced densities to uncertainties inherent to the calculation method was also examined, with the bulk of the errors due to uncertainties in FUV imager data and choice of distribution function for precipitation energy spectra. Plain Language Summary: The Empirical Canadian High Artic Ionospheric Model (E‐CHAIM) is a measurement‐based model which provides the electron density of the upper atmosphere (the ionosphere) for a user‐specified date, time, and location at northern high latitudes (>50° geomagnetic latitude). The Earth's ionosphere can aid or disrupt the operation of technologies such as global navigation and radio communication systems, and thus ionosphere models are a critical component for reliable operation of these systems. E‐CHAIM is currently the most reliable model for high‐latitude ionosphere densities, which are particularly dynamic and complex due to the vertical orientation of Earth's high latitude magnetic field. A lack of reliable, widespread observations of the lower ionosphere (at roughly 95–200 km altitude) has resulted in deficiencies in E‐CHAIM at these altitudes, mainly an inability to capture enhanced ionosphere densities associated with the precipitation of energetic particles that travel from near‐Earth space, along Earth's magnetic field, and down into the atmosphere. To address this model deficiency, we have used satellite ultraviolet imager data as an indirect means of estimating enhanced ionosphere densities. Comparison of E‐CHAIM densities with ground‐based ionosphere density measurements has revealed that integration of these satellite‐derived densities into E‐CHAIM significantly improves model performance. Key Points: Satellite ultraviolet imager (UVI) measurements are used to develop a precipitation component for the Empirical Canadian High Arctic Ionospheric Model for high‐latitude ionosphere density Comparisons with incoherent scatter radar measurements reveal significant improvement in density representation at 95–200 km altitude Precipitation enhanced densities are most sensitive to errors in satellite UVI data and selected electron energy spectrum